2012
DOI: 10.1002/arch.21042
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION OF THE WESTERN TARNISHED PLANT BUG (Lygus hesperus) OLFACTORY CO‐RECEPTOR ORCO: EXPRESSION PROFILE AND CONFIRMATION OF ATYPICAL MEMBRANE TOPOLOGY

Abstract: Lygus hesperus (western tarnished plant bug) is an agronomically important pest species of numerous cropping systems. Similar to other insects, a critical component underlying behaviors is the perception and discrimination of olfactory cues. Consequently, the molecular basis of olfaction in this species is of interest. To begin to address this issue, we utilized homology‐based PCR as a commonly accepted abbreviation but if necessary it is polymerase chain reaction methods to identify the L. hesperus olfactory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 78 publications
5
16
0
Order By: Relevance
“…All 4 protein sequences were predicted to possess seven transmembrane domains and they were highly divergent, with amino acid sequence identities of 20-30% when compared with ORs from different species (Fig. 1) (Supplementary material S2), a common phenomenon observed between insect ORs within and between species (Cao et al, 2014;Hull et al, 2012;Sparks et al, 2014;Zhou et al, 2014), except for the pheromone receptors (PRs) in Lepidoptera insects and Orco (Vosshall and Hansson, 2011;Grosse-Wilde et al, 2011;Liu et al, 2012;Zhang et al, 2013b).…”
Section: Gene Cloning and Sequence Analysis Of A Lucorum Orsmentioning
confidence: 99%
“…All 4 protein sequences were predicted to possess seven transmembrane domains and they were highly divergent, with amino acid sequence identities of 20-30% when compared with ORs from different species (Fig. 1) (Supplementary material S2), a common phenomenon observed between insect ORs within and between species (Cao et al, 2014;Hull et al, 2012;Sparks et al, 2014;Zhou et al, 2014), except for the pheromone receptors (PRs) in Lepidoptera insects and Orco (Vosshall and Hansson, 2011;Grosse-Wilde et al, 2011;Liu et al, 2012;Zhang et al, 2013b).…”
Section: Gene Cloning and Sequence Analysis Of A Lucorum Orsmentioning
confidence: 99%
“…Those data have since been supplemented with recent genome and EST-based OBP projects in aphids , the lucerne plant bug (Adelphocoris lineolatus) (Gu et al, 2011a), the green plant bug (Apolygus lucorum) (Gu et al, 2011a;Hua et al, 2012), and the brown planthopper (Nilaparvata lugens Stål) (Noda et al, 2008;Xu et al, 2009;He et al, 2011). Our understanding of the molecular components comprising the Lygus olfactory system is even more incomplete with sequence and expression data currently limited to Lygus antennal protein (LAP), a 'classic' OBP preferentially expressed in adult male L. lineolaris and L. hesperus antennae (Dickens et al, 1995(Dickens et al, , 1998Vogt et al, 1999), and the recently identified Lygus OR coreceptor (Hull et al, 2012). To derive a better molecular understanding of olfaction in L. lineolaris (and Lygus spp.…”
Section: Introductionmentioning
confidence: 99%
“…For GRs, the prediction of the transmembrane domains is less clear-cut because not all of the domains are as prominently hydrophobic as most transmembrane proteins such as GPCRs, channels, and transporters, and various transmembrane prediction programs regularly under-predict them and sometimes over-predict them; they consequently also often indicate the incorrect orientation in the membrane (e.g., Benton et al, 2006;Smart et al, 2008;Zhang et al, 2011;Hull et al, 2012). The orientation in the membrane is known for the conserved Odorant Receptor Co-Receptor or Orco protein and other ORs (Benton et al, 2006;Lundin et al, 2007;Smart et al, 2008;Tsitoura et al, 2010;Hull et al, 2012), which are clearly related to the GR family in the insect chemoreceptor superfamily (Robertson et al, 2003), as well as for one GR (Zhang et al, 2011). It is the opposite of the GPCR orientation, with the N-terminus internal to the cell.…”
Section: Delimiting Functional Domainsmentioning
confidence: 99%